2013
DOI: 10.2298/sarh1308511s
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and C-reactive protein in patients with depressive disorder on antidepressive medication

Abstract: Both CRP levels and metabolic risk profile screening, according to the international criteria, may be beneficial in order to obtain better assessment for depressive long-term medicated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 26 publications
0
20
1
Order By: Relevance
“…Some authors showed a positive correlation and normalization of these values after therapy with antidepressants [ 59 , 60 ]. However, these finding were not consistent with negative findings from other studies in this field [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some authors showed a positive correlation and normalization of these values after therapy with antidepressants [ 59 , 60 ]. However, these finding were not consistent with negative findings from other studies in this field [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…CRP is one of the positive acute-phase proteins, secreted in the liver. Depression has been shown to be associated with the increased inflammatory response [ 52 ]. Also, it has been suggested that the link between depression, obesity, and diabetes may be mediated through inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Stanojevic et al [ 83 ] showed the levels of total cholesterol, low-density lipoprotein cholesterol, triglycérides and blood pressure were statistically significantly elevated in the depressive patients with metabolic syndrome compared with healthy controls. Moreover, in other studies, hypercholesterolemia was linked to the poor outcome of antidepressant therapy in depression.…”
Section: Discussionmentioning
confidence: 99%
“…The PubMed literature search identified 36 articles. After title, abstract, and eventually full-text screening, 8 papers ( 1 , 37 43 ) met inclusion criteria for this mini-review (see Figure 1 for more details) ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8 studies included in our mini-review, 2 used a prospective cohort design ( 37 , 41 ), and 6 a cross-sectional design ( 1 , 38 40 , 42 , 43 ). In 3 studies the number of participants was ≤ 99 ( 38 , 40 , 43 ), 2 studies had a sample ranging from 100 to 240 individuals ( 37 , 41 ), 3 studies included more than 250 patients ( 1 , 39 , 42 ). The average number of participants was of 277 ± 296 (SD) (min 60, max 970 participants).…”
Section: Resultsmentioning
confidence: 99%